2019
DOI: 10.3389/fncel.2019.00165
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Pain Processing in the Rat Anterior Cingulate Cortex and Primary Somatosensory Cortex

Abstract: Pain is a complex multidimensional experience encompassing sensory-discriminative, affective-motivational and cognitive-emotional components mediated by different neural mechanisms. Investigations of neurophysiological signals from simultaneous recordings of two or more cortical circuits may reveal important circuit mechanisms on cortical pain processing. The anterior cingulate cortex (ACC) and primary somatosensory cortex (S1) represent two most important cortical circuits related to sensory and affective pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 56 publications
6
45
0
Order By: Relevance
“…Shih and colleagues (2019) have recently demonstrated that ACC theta power is decreased, while motor cortex theta power is increased following lesion of the medial thalamic nuclei, a region thought to convey affective elements of pain. Likewise, decreases in Theta and Alpha power following application of a noxious, mechanical probe are evident in the ACC but not S1 (Xiao et al, 2019). Thus, discrepancies in the direction of oscillatory changes may reflect real, physiological differences in how distinct brain regions respond to persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Shih and colleagues (2019) have recently demonstrated that ACC theta power is decreased, while motor cortex theta power is increased following lesion of the medial thalamic nuclei, a region thought to convey affective elements of pain. Likewise, decreases in Theta and Alpha power following application of a noxious, mechanical probe are evident in the ACC but not S1 (Xiao et al, 2019). Thus, discrepancies in the direction of oscillatory changes may reflect real, physiological differences in how distinct brain regions respond to persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…4d), suggesting that while S1 encodes the sensory‐discriminative components of pain during noxious and non‐noxious peripheral stimulation, it may not play a role in pain in the absence of a stimulus in this model of neuropathy. The S1 may be implicated in spontaneous somatosensory sensations in the absence of noxious stimuli since an S1 lesion in the rat alters pain affect and cortical recordings indicate event‐related potentials in the S1 during spontaneous pain episodes . Nevertheless, studies are needed to fully elucidate the role of S1 in non‐evoked pain due to neuropathic injury.…”
Section: Discussionmentioning
confidence: 99%
“…During the inter-trial intervals, we examined the rat’s behavior to identify putative spontaneous pain episodes (such as twitch, lifting/flicking, paw withdrawal and paw licking). Due to the lack of ground truth, we referred to those events as spontaneous pain-like episodes [26].…”
Section: Methodsmentioning
confidence: 99%
“…For multisite recordings, it is important to investigate the inter-regional local field potential (LFP) oscillatory coordination [22], as interareal oscillatory synchronization plays an important role in top-down neocortical processing [23]. In a series of rodent pain experiments, we collected various in vivo neurophysiological data (spikes and LFP) from single or two brain regions in freely behaving rats [7, 2426]. These data have established the foundation towards improved understanding of pain perception as well as empirical evidence for computational modeling.…”
Section: Introductionmentioning
confidence: 99%